Impact of C-reactive protein on the effect of Roxadustat for the treatment of anemia in chronic kidney disease: a systematic review of randomized controlled trials - Xiaoyu Luo; Guoli Li; Hongyu Yang; Lang Chen; Yinyan Gao; Jing Cong; Hui Luo; Weiru Zhang (BMC Nephrology, 2024)
Abstract Background Chronic inflammation, reflected by an increased blood C-reactive protein (CRP) level, is common in patients with chronic kidney disease (CKD) and is involved in the development of renal anemia. This systematic review aims to investigate the impacts of CRP on the efficacy of hypoxia-inducible factor-prolyl hydroxylase inhibitors (HIF-PHIs) in the treatment of renal anemia in patients with CKD. Methods We conducted a comprehensive search of electronic databases including Pubmed, Web of Science, Embase, Cochrane Library, CNKI, Wanfang, and the International Clinical Trials Registry Platform (ICTRP), from their inception to May 19, 2022. We systematically reviewed evidence from randomized controlled trials using HIF-PHIs for renal anemia treatment. The mean difference (MD) in changes in hemoglobin concentration (∆Hb) before and after treatment served as the meta-analysis outcome, utilizing a random-effects model. We compared groups with CRP levels greater than or equal to the upper limit of normal (ULN) and less than the ULN. Additionally, further analysis was conducted in the CRP ≥ ULN group comparing HIF-PHIs and erythropoiesis-stimulating agents (ESA). Results A total of 7 studies from 6 publications were included in the analysis. In the comparison between the CRP ≥ ULN group and the CRP < ULN group, 524 patients from 4 studies were incorporated into the analysis. All patients received roxadustat as the primary intervention. The pooled results revealed no significant difference in ΔHb between patients with CRP ≥ ULN and CRP < ULN at baseline (Mean Difference: 0.00, 95% Confidence Interval: -0.32 to 0.33, P = 0.99). Moreover, within the CRP ≥ ULN group, three studies involving 1399 patients compared the efficacy of roxadustat and erythropoiesis-stimulating agents (ESAs). The results indicated no significant difference in ΔHb between patients treated with ESAs and HIF-PHIs (Mean Difference: 0.24, 95% Confidence Interval: -0.08 to 0.56, P = 0.14). In terms of medication dosage, an increase in ESA dose over time was observed across various studies, particularly evident in the CRP ≥ ULN group, while the dose of roxadustat remains constant over time and is not influenced by the baseline levels of CRP. Conclusions Our systematic review demonstrates that roxadustat exhibits similar efficacy across different CRP levels. Moreover, within the CRP ≥ ULN group, roxadustat can maintain efficacy comparable to ESA without the necessity for dose escalation. Trial registration CRD42023396704.